Thermoforming : improving process performance - Rosen, Stanley R. (Society of Manufacturing Engineers : Plastics Molders & Manufacturers Association of SME, 2002)
Thermoforming is a processing technique involving air pressure applied to heated plastic, and combines the earlier terminology of vacuum-formed and pressure-formed operations. A specialist in thermoforming, mechanical engineer Rosen describes the roll-fed process, properties of plastic materials, designing products, thermoforming machines, trim presses, knife-like trim dies, and off-line punch-and-die trimming. Chapters on molds cover mold design, system components, layout and base design, and cost estimating. Annotation copyrighted by Book News, Inc., Portland, OR.